Home-based exercise during confinement in COVID-19 pandemic and mental health in adults: a cross-sectional comparative study - Luiz José Frota Solon Júnior; Leonardo de Sousa Fortes; Bruno Teixeira Barbosa; José Valdir Alves Feitosa Júnior; Carlos Henrique Tomaz Ribeiro; Luiz Vieira da Silva Neto (Revista Brasileira de Atividade Física e Saúde)
This study compared the quality of life, sleep quality, eating attitudes, and psychological aspects among adults (22.93 ± 2.58 years), whether physically inactive or not, before and during the COVID-19 pandemic. Participants were enrolled into: home-based exercise during the confinement (HBE group, n = 34), physically inactive during (PIDC group, n = 28), and before the confinement (PIBC group, n = 27). The depression, anxiety, and stress scale - Short Form, the Pittsburgh sleep quality index, the Eating Attitudes Test, and the quality of life questionnaire were used to assess variables. The covariance analysis (covariable - gender) was used to compare variables among the groups. The effect size was calculated by Cohen "d" (ESd). The HBE group presented a better quality of life compared to both PIDC (p = 0.002, ESd = 1.26) and PIBC (p = 0.008, ESd = 1.00) groups. Anxiety (p = 0.004, ESd = 0.96), depression (p = 0.02, ESd = 0.65) and stress (p = 0.02, ESd = 0.72) were significantly higher in the PIDC group when compared to HBE group. Self-reported sleep quality was better in the HBE group than in both other groups (p < 0.05). No group presented eating disorder symptoms; however, the HBE group has shown higher scores compared to both PIBC group (p = 0.01). In conclusion, adults who had exercised at home during the COVID-19 pandemic presented better quality of life, self-reported sleep quality, and reduced anxiety, depression, and stress levels than those physically inactive ones before and during the pandemic.